2013
DOI: 10.3126/on.v11i1.8245
|View full text |Cite
|
Sign up to set email alerts
|

Food and Feeding Habits of the Mola Carplet Amblypharyngodon mola (Hamilton, 1822) in Rice Field Ecosystem with Consideration of Water Quality Parameters

Abstract: The present investigation was conducted in the Agronomy field laboratory of Bangladesh Agricultural University, Mymensingh, Bangladesh during May 1999 to August 1999 to reveal the food and feeding habits of Amblypharyngodon mola in the rice field ecosystem. Percentage of frequency of occurrence and percentage in number methods were used for the qualitative and quantitative estimation of plankton population. Results showed that, during the present study, the water quality parameters were within the suitable ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Besides Chlorophyceae, the fish also feeds on Cyanophyceae, Bacillariophyceae, and Euglenophyceae (Mamun, Tareq, & Azadi, 2004;Mondal et al, 2013;Nandi & Saikia, 2015;Suresh, Biswas, Vinci, Mitra, & Mukherjee, 2007). With this information on food and feeding of A. mola, it is not known whether it feeds passively through filter feeding or passionately through gustatory or sensory judgment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides Chlorophyceae, the fish also feeds on Cyanophyceae, Bacillariophyceae, and Euglenophyceae (Mamun, Tareq, & Azadi, 2004;Mondal et al, 2013;Nandi & Saikia, 2015;Suresh, Biswas, Vinci, Mitra, & Mukherjee, 2007). With this information on food and feeding of A. mola, it is not known whether it feeds passively through filter feeding or passionately through gustatory or sensory judgment.…”
Section: Introductionmentioning
confidence: 99%
“…Nandi and Saikia (2015) worked on the feeding behavior of A. mola and revealed that the fish is herbivorous in nature, and feeds mainly on phytoplankton especially Chlorophyceae (Nandi & Saikia, 2015). Besides Chlorophyceae, the fish also feeds on Cyanophyceae, Bacillariophyceae, and Euglenophyceae (Mamun, Tareq, & Azadi, 2004; Mondal et al, 2013; Nandi & Saikia, 2015; Suresh, Biswas, Vinci, Mitra, & Mukherjee, 2007). With this information on food and feeding of A. mola , it is not known whether it feeds passively through filter feeding or passionately through gustatory or sensory judgment.…”
Section: Introductionmentioning
confidence: 99%
“…Species specific information of feeding ecology is still rare. In fisheries management and aquaculture practices, food and feeding habits of fishes have great importance [6] for knowing the population level, growth rate and condition of fishes, which helps the fish farmers to have the clear idea about fish dietary requirements to reduce intra-specific and inter-specific competition of fishes in the habitat [7,8]. Moreover, data on the feeding habits of marine fishes, such as the predatory-prey relationship are very helpful in the ecosystem [9].…”
Section: Introductionmentioning
confidence: 99%
“…Mondol et al . () recorded Chlorophyceae followed by Bacillariophyceae as the dominant and preferred food groups of A. mola in rice fields. More interesting are the common occurrences of the small and colonial forms of phytoplankton belonging to Chlorophyceae and Cyanophyceae in the gut of A. mola, which indicate the non‐generalist and specialist feeding nature of the fish.…”
Section: Discussionmentioning
confidence: 99%